Quality control of Bradyrhizobium inoculant strains: detection of nosZ and correlation of symbiotic efficiency with soybean leaf chlorophyll levels - Brignoli, Damián (2024)
Greenhouse gas emissions, such as N2O from excessive N-fertilizer use, are of concern. Symbiotic N2-fixation by pulses such as soybean might mitigate this issue, for which inoculants carrying locally adapted Bradyrhizobium strains are recommended. In the frame of this goal, enhancing the quality control of these inoculants is required on two key aspects: determining the presence of nosZ, for the strains being able to reduce N2O, and assessing N2- fixation potential. Previously it was demonstrated that, in soybean leaves, Ncontents are well correlated with chlorophyll contents. However, no such correlations were made with either N obtained from N2-fixation or with nodules mass, which is an indicator of nodular activity. Here we aimed to leverage the correlation between N and chlorophyll levels to develop a simple and non-destructive laboratory method to be applied in quality control of inoculants, able to assess the N2-fixing capacity of rhizobial strains. To establish such correlations, we cultivated soybeans in vermiculite with N-free nutrient solution, and inoculated them with various Bradyrhizobium field isolates that displayed a range of symbiotic N2-fixing capacities. Subsequently, we measured chlorophyll with a portable chlorophyllometer, and correlated these measures with symbiotic parameters. Moreover, we tested for the presence of nosZ by PCR. We observed significant correlations between chlorophyll and shoot nitrogen obtained from N2-fixation and, in addition, we corroborated that chlorophyll contents were significantly correlated also with nodules mass. Two B. diazoefficiens strains stood out and possessed nosZ. In contrast, B. elkanii and B. japonicum isolates displayed lower chlorophyll and symbiotic performance, and lacked nosZ. Our findings highlight the potential of measuring chlorophyll contents and testing for the presence of nosZ as two straightforward techniques that may enhance laboratory tests for quality control, enabling selection of superior and safe locally isolated strains for soybean inoculants without increased production costs.